Global Mentoring Circle Program (GMCP) Factors on the Effectiveness of GMCP: The Case of Dell Technologies - Tan, Yoke Ching (2023)
Technology is advancing exponentially, and those who can adapt quickly and successfully will prosper in this uncertain world. Studies have shown that investing in people development will increase performance and productivity, increase engagement and retention and increase in innovation and creativity. This research will be a case study on understanding an internal program called Global Mentoring Circle Program (GMCP) in Dell Technologies. GMCP was launched 2 years ago and there is no sufficient evidence data to determine what factors have a significant relationship to the effectiveness of the program. GMCP is a group mentoring program where there are 7-8 mentees to a mentor. When the program ends, the mentees will be invited to take the survey to so that the writer can provide a recommendation to the President. A pilot was conducted by inviting 140 managers to join, 127 managers accepted, and 81 managers responded to the survey. The 4 independent variables were tested, which are structure, content, mentor, and mentee. Based on the statistical data, the results show that the data sets were reliable. Using Pearson’s Correlation Analysis, the results show that the structure, mentor and mentee have a strong correlation with the effectiveness whereas the content has a weaker correlation with the effectiveness of the program. Multiple regression analysis reveals that the mentor has the strongest relationship, followed by mentees and structure factors. It is also concluded that the content has little bearing on the GMCP's effectiveness. On the effectiveness of the GMCP in their development, 92% of the participants “agree” and “strongly agree” that the program was effective to their development. In summary, the pilot is very successful, and the writer will recommend to the President to go ahead with the program at the global level. Besides that, the framework can be used in any industry and any organization globally. In this regard, this research can be a piece of valuable information to the organization as well as to future researchers in similar areas.